Study of recycling printed circuit boards: alternative methods to attach components in printed circuit boards (2014)
Printed circuit boards (PCB), which form the basis of the electronics industry, generate wastes that are difficult to dispose of and recycle due to the diversity of their materials and components and their difficult separation. The replacement of Pb-Sn welding for lead-free alloys to attach components in printed circuit boards is an attempt to minimize the problem of Pb toxicity, but it does not change the problem of separation of the components for later reuse and/or recycling. This article presents a review of the environmental problem of printed circuit boards, the initial development of alternative fixation studies, and reliability tests for comparison with conventional boards and commercial systems to validate or serve as a basis for future research, focused on PCB disassembly for recycling. At present, initial studies were performed by using prototypes for visual and functional tests.